Fazril Transportation Service / Muhammad Ezril Fitri Mohd Kamrulnezam and Muhammad Fahim Subly - Mohd Kamrulnezam, Muhammad Ezril Fitri; Subly, Muhammad Fahim (2023)
In this subject, Principle of Entrepreneurship (ENT530), we learn about Copywriting strategy. From the Social Media Report, students need to choose a product or services to promote for selling on the social media such as Facebook. As we know, most people had their own social media account to connected with others. Facebook is one of the best platforms that we can use to do an online business. FAZRIL TRANSPORTATION SERVICE is our service name that we decided to promote and provide the transportation service on Facebook page. We choose this service because many people espacially student in UiTM Puncak Alam need a transport to go everywhere they want. We used Perodua Axia as the main car because it is efficient and reliable to use. We named our service FAZRIL because it is our combination name between FAHIM and EZRIL as a partnership for this business and also easy to remember it. Additionally, our service also open for the public. The name chosen is also intended to attract the attention of customers. There are two types of copywriting techniques that we used to promote our online product and this business. Soft sell copywriting is a soft sell which features are more suitable language, consultative tone, and non-aggressive technique. This technique is used to attract more customer and persuade them to buy our product. It also helps to create awareness and provide updates about the product. The other copywriting technique is hard sell is a direct and insistent language of advertising. It can be consisted as a high-pressure and aggressive technique to persuade customer in the short-term.